Hospital safety preparedness during the COVID-19 pandemic: Lessons learned from Vietnam - Thu, Nguyen Thi Hoai; Anh, Bui Thi My; Khanh, Luong Bao; Anh, Pham Tran; Luong, Duong Huy (Frontiers in Tropical Diseases, 2022)
Introduction: The rapid spread of SARS-CoV-2, varying vaccine coverage and appearance of new variants posed a significant threat during the pandemic, especially in LMIC countries. Hospitals in Vietnam at both central and local levels have had cross-infection of patients and healthcare workers. Therefore, providing a safe and secure environment for staff and patients was a major focus for all health care institutions. Methods: We conducted a cross-sectional study, using both quantitative and qualitative methods, to answer the question how the hospital safety during the COVID-19 pandemic in Vietnamese hospitals implemented and what the challenges were. Secondary data from a recent national survey of safety in 1398 hospitals conducted by Vietnam Ministry of Health (MOH) were extracted and analyzed. In-depth interviews of key health managers and health staff in 4 selected hospitals were performed to further explore challenges in implementing the Decision 3088/QD-BYT. Results: The proportion of hospitals classified as “safe hospital” was 91.7%, “safe hospital with moderate level” was 7.3% and “unsafe hospital” was 1.0%. The rate of “safe hospital” was highest in the central level hospitals (96.1%), followed by private hospitals (94.4%), provincial hospitals (94.2%), specialized hospitals (93.1%), regional hospitals (93.0%) and district hospitals (89.9%) while “safe hospital” rates were lowest in the ministerial level hospital group (82.2%). Challenges in ensuring hospital safety in public and private hospitals related to COVID-19 transmission were explored regarding lack of preparedness before COVID-19 and other pandemics, limited hospital facility, limited space and equipment, shortage of human resources, inadequate training and knowledge transfer; poor patient compliance in declaring health conditions and lack of patient understanding of infection prevention methods. Conclusion: Most hospitals in Vietnam successfully met the classification of “safe hospitals” according to the Decision 3088/QD-BYT; a key tool for hospitals to self-assess preparedness and responsiveness to the COVID-19 pandemic. MOH should adapt the criteria in Decision 3088/QD-BYT to be more suitable with the new phase of the pandemic as we move towards “living with COVID”. Furthermore, we recommend that MOH work to develop mechanisms or regulations that require hospitals to regularly report on disease preparation and responses for future pandemic preparedness.